Sex differences in factors associated with poor subjective sleep quality in athletes - Kawasaki, Y.; Kasai, T.; Koikawa, N.; Hanazato, N.; Suda, S.; Murata, A.; Ozaki, R.; Nagai, S.; Matsumura, Y.; Kaneko, H.; Kubo, M.; Osawa, A.; et al. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Sleep is an important recovery period for athletes. In general, women are not satisfied with their sleep quality, which is also true for female soccer players, although the reasons remain to be elucidated. This study aimed to confirm sex difference in sleep quality among athletes from various fields of sport, and to investigate factors related to poor subjective sleep quality in male and female athletes. METHODS: We collected data concerning subjective sleep quality, measured by Pittsburgh Sleep Quality Index (PSQI), from athletes who were 16 to 40 years of age and played various types of sports. Data concerning their sports, lifestyle, and sleep issues and sleep environments, and also menstrual issues for females, were collected. RESULTS: Data from 207 male athletes and 215 female athletes were assessed. Among them, 31.4% of men and 48.8% of women had poor subjective sleep quality (i.e., PSQI=6). In male athletes, witnessed apnea, episodes of disorientation or confusion during the time of sleep, long time gap between dinner and bedtime, and turning on the heating in the winter, were identified as factors associated with poor sleep quality by multivariate analysis, whereas in female athletes, bathing close to bedtime, habitual drinking, and being annoyed by noises at bedtime were identified. CONCLUSIONS: In both populations, females had poorer subjective sleep quality than males. Sex differences exist in factors associated with poor subjective sleep quality. Thus, different approaches should be considered to improve their sleep quality.